The effect of social jet lag on burnout in portuguese aeronautic shift workers - Dézsenyi, Fanni (2022)
This cross-sectional study aimed to examine the levels of social jetlag (SJL) and burnout and if SJL can predict burnout. For this we used a sample of 348 workers from the aeronautic field (aircraft maintenance technicians) working in regular shift schedule, in a morningevening shift structure, or in a rotating night – evening - morning shift condition in a Portuguese company. In this study we use the Munich ChronoType Questionnaire - MCTQShift , the Oldenburg Burnout Inventory and the Karasek’s Job Content Questionnaire to measure chronotype, SJL, burnout and stress at work of the workers. Results suggested that working in shifts increased the possibility of having SJL as described previously. Moreover, individuals with late chronotype were more likely to have SJL as well as those working in 3 shifts, while sleep duration was not a significant factor for circadian misalignment. Burnout score was higher for those working in 3 shifts, and it was also predicted by social jetlag, age and stress at work. However, in this specific sample, all 3 groups showed elevated levels of burnout. This raises questions and opportunities for improving workers’ health and well-being by implementing measures for reduce circadian strain and stress levels optimizing working conditions of the aeronautic maintenance technicians. The sample has its limitations due to the self-report measures, and its specificities (less women and less regular workers), however, the study prompts further research to find the real underlying causes of burnout, and to disentangle the specific predictors of this multidimensional phenomenon.